Van Dijk’s critical discourse analysis in the Narasi Mata Najwa program and the community response to the face-to-face learning in Indonesian - Ryan Hidayat; Khusnul Khotimah; Sumarlam Sumarlam (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
The purpose of this study is to analyze the critical discourse of Teun A. Van Dijk's model in the Narasi Mata Najwa program. The Narasi Mata Najwa program is a strategic forum for social groups, community groups to appear and discuss the discourses presented. The Narasi Mata Najwa program often invites figures from various circles of society, both from government figures and political figures. The Narasi Mata Najwa event is a discourse formation practice. Discourse refers to social activities that take place from various backgrounds in which the language unit appears. Critical discourse analysis using Van Dijk's model includes three aspects, namely macro structure, super structure, and microstructure. This research uses descriptive qualitative research method. The results of this research from Van Dijk's model examines the discourse that is used as a suggestion for opinion formation through word choice, sentence structure, and appropriate language style.Keywords: critical discourse analysis, Narasi Mata Najwa, community response